2016
DOI: 10.1080/1028415x.2015.1103460
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury effectively ameliorated by neuroprotective effects of rosmarinic acid

Abstract: The study demonstrates for the first time on the role of RA in protecting the spinal cord from injury and demonstrates its neuroprotection in wistar rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…RosA inhibited neuronal apoptosis through targeting ROS and inflammatory responses in SCI. (Shang et al, 2017) Experimental diabetes with cerebral ischemia…”
Section: Effect Of Rosmarinic Acid On Other Inflammatory Diseasesmentioning
confidence: 99%
“…RosA inhibited neuronal apoptosis through targeting ROS and inflammatory responses in SCI. (Shang et al, 2017) Experimental diabetes with cerebral ischemia…”
Section: Effect Of Rosmarinic Acid On Other Inflammatory Diseasesmentioning
confidence: 99%
“…These plants may also enhance cognitive abilities and improve psychiatric and behavioral symptoms of dementia (Akhondzadeh et al, 2003;Perry, Bollen, Perry, & Ballard, 2003). Findings have also shown that the use of medicinal plants for the treatment of VaD and other neurodegenerative disease such as Parkinson may be beneficial because some of them, due to antioxidant properties, prevent neuronal loss and neurodegeneration (Kalaria et al, 2008;Shang et al, 2017;Sheu & Wu, 2017). It is also suggested that targeting the autophagylysosome pathway by using herbal products may be considered as a therapeutic option for Parkinson's disease (da Costa et al, 2017;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Various drugs exert antioxidative neuroprotective activities in the spinal cord by activating Nrf-2 such as asiatic acid, rosmarinic acid and resveratrol [ 12 25 26 27 ]. In Wistar rats, carnosol protects against SCI-induced oxidative stress and inflammation by modulating nuclear factor-κB, cyclooxygenase-2, and Nrf-2 levels [26].…”
Section: Discussionmentioning
confidence: 99%